Gold - Silver Nexus: A Threshold Cointegration Approach - Mighri, Zouheir Ahmed; Al Saggaf, Majid Ibrahim (International Journal of Economics and Financial Issues, 2018)
We investigate the dynamic relationship between the gold and silver prices using the Enders-Siklos threshold cointegration approach. Our data are the weekly prices of the gold and silver from January 1968 to May 2016. We find a, asymmetric threshold cointegration between these two series, instead of the linear cointegration well established in the literature. The short-term adjustment to the equilibrium shows an asymmetric effect according to the price deviation from the long-run equilibrium. Moreover, using an equilibrium adjustment path asymmetry test, we find that, in the short term, gold has a much faster reaction to negative deviations from long-term equilibrium than positive deviations. Keywords: Threshold cointegration; price transmission; gold; silver JEL Classifications: C13, C22, C32, C52, C53, G15